WORKSHOP DAN PEMBINAAN SUMBER DAYA MANUSIA DALAM PENYUSUN LAPORAN KEUANGAN KOPERASI SMAM 8 MOROWUDI GRESIK - Afiqoh, Nyimas Wardatul; Syaiful, Syaiful (Universitas Muhammadiyah Gresik, 2023)
The purpose of this activity is to increase knowledge and adherence to cooperative principles and cooperative business development at Muhammadiyah 8 Morowudi Gresik High School. This activity program is funded by Muhammadiyah University of Gresik. The implementation of these activities is carried out by holding training and mentoring on cooperative principles, basic training on the resources available in the cooperative. Bookkeeping and accounting training activities were held on Wednesday, August 12, 2022. The Basic Accounting and finance training was carried out by involving the chairman, treasurer, and secretary of the cooperative as well as the cooperative operational division and cooperative finance staff at SMA Muhammadiyah 8 Morowudi Gresik.